Decentralization Reform in Ukraine: Assessment of the Chosen Transformation Model - Udovychenko, Volodymyr; Melnychuk, Anatoliy; Gnatiuk, Oleksiy; Ostapenko, Pavlo (European Spatial Research and Policy, 2017)
Ukraine has to reform the spatial organization of power, which involves alteration of the administrative-territorial division in very difficult socio-economic and political conditions. Despite a great interest in the Ukrainian decentralization reform in scientific publications and media, the influence of chosen voluntary consolidation mode on the newly formed territorial communities, including their spatial configuration, economic potential and institutional capability, remains uncovered. Trying to shed some light on the issue, the authors made an attempt to reveal advantages and disadvantages of the selected model of reform on the example of the Perspective Plan of Territorial Communities Formation in Kyiv Region.